The Application of Peer-Assisted Study Sessions (PASS) to Teach Writing at Students of Class Eight of SMP Negeri Sempol Bondowoso - Nostalgianti Citra Prystiananta (Linguistic, English Education and Art (LEEA) Journal, 2018)
The study aims at finding out whether or not it is effective to use PASS write model to teach writing at students of class eight of SMP Negeri Sempolin Academic Year 2016/2017. The population of students of class eight of SMP Negeri Sempol with the sample class VIIIB consist 27 students. The research was a preexperimental research by applying one group of pretest and posttest design. In collecting the data, the writer used the written test that was administered in pretest and posttest. The data analysis was conducted through calculating the individual score, convert students score with schools passing grade, and calculating ttest. The results show that in the pretest, the students mean was 69.29. On the other hand, in the posttest their scores increased to 75.67. The result of paired ttest calculation presented the ttest score was 7.25 and the significance level was 0.05 with the df 26 (27 to 1) (1.703). It means that ttest score was higher than its tscore. Finally, it can be concluded that it was effective to teach writing skill through Peer Assisted Study Sessions to students of class eight of SMP Negeri Sempol Bondowosoin Academic Year 2016/2017. Keywords: teaching writing,peer assisted study session, PASSwrite